2019
DOI: 10.1021/acs.jmedchem.9b01560
|View full text |Cite
|
Sign up to set email alerts
|

Docking Finds GPCR Ligands in Dark Chemical Matter

Abstract: High-throughput screening has revealed dark chemical matter, a set of drug-like compounds that has never shown bioactivity despite being extensively assayed. If dark molecules are found active at a therapeutic target, their extraordinary selectivity profiles make excellent starting points for drug development. We explored if ligands of therapeutically relevant G-protein-coupled receptors could be discovered by structure-based virtual screening of the dark chemical matter. Molecular docking screens against crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Optimized virtual library Despite the vast chemical space (>10 63 drug-like molecules), only a nominal fraction has been explored by SBDD, where both the compound availability and insufficient diversity limited the number of screened ligands. To overcome these problems, ultralarge [208][209][210] and focused libraries [211][212][213] were employed. Lyu and colleagues 208 presented an excellent model of "bigger is better" in virtual drug screening.…”
Section: Structure-based Drug Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Optimized virtual library Despite the vast chemical space (>10 63 drug-like molecules), only a nominal fraction has been explored by SBDD, where both the compound availability and insufficient diversity limited the number of screened ligands. To overcome these problems, ultralarge [208][209][210] and focused libraries [211][212][213] were employed. Lyu and colleagues 208 presented an excellent model of "bigger is better" in virtual drug screening.…”
Section: Structure-based Drug Designmentioning
confidence: 99%
“…A follow-up study on MT 1 by docking >150 million "leadlike" molecules 209 identified 15 active leads (39% hit rate) with potencies ranging from 470 pM to 6 μM. Alternatively, focused library [210][211][212][213][214][215] including scaffold library, natural products, dark chemical matter (i.e., chemicals that have never shown bioactivity tested in over 100 assays), and fragment-and lead-like libraries were introduced in virtual screening (VS) for dozens of receptors. Focused on compound library of traditional Chinese medicine (TCM), Liu et al found that salvianolic acids A and C antagonized the activity of both P2RY1 and P2RY12 purinoceptors in the low µM range, while salvianolic acid B antagonized the P2RY12 purinoceptor.…”
Section: Structure-based Drug Designmentioning
confidence: 99%
“…29 Even though DCM has a low activity prole against common targets, the rationale of screening this collection was to explore regions in chemical space currently overlooked. Moreover, DCM has yielded active molecules in other assays 31,32 probing the value of screening this region of the chemical space. The structures of FooDB and DCM were curated and standardized, employing RDKit, CDK (Chemistry Development Kit), and ChemAxon tools.…”
Section: Methodsmentioning
confidence: 99%
“…Leurs also co-founded Griffin Discoveries (http://www.griffindiscoveries.com/), a company that has leveraged this GPCR expertise and is currently involved in the discovery and development of novel GPCR ligands. Carlsson has utilized the available structural information for extensive virtual screening driven drug discovery exercises for multiple targets (Ballante et al, 2020;Rodríguez et al, 2014). In particular, Carlsson utilizes physics-based methods such as molecular dynamics simulations and molecular docking to focus on how small molecules interact with GPCRs and thereby modulate their function.…”
Section: Examples Of Structure-based Drug Design For Gpcrsmentioning
confidence: 99%